Analisis Kantin Sekolah SD Negeri Mangunsari 03 Salatiga Berdasarkan Kebijakan Pemerintah - Patricia, Patricia; Christian, Reuhel; Pritayanti, Herniana Noer; Lamaliwa, Wynda Lestari (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Backgroud: Children prevalence on nutrition double burden condition in Indonesia remains high. Children prevalence under 5 years old for malnutrition is 19.7% while stunting is 37.2%, and combination between overweight and obesity is 11.9%. One way to solve this condition is through school canteen. School canteen can become solution because one purpose of school canteen is to make their student become healthy children. The importance of school canteen make school canteen in SD Negeri Mangunsari 03 Salatiga that already did healthy canteen require deep analysis toward existed government policy. Method: this research used qualitative methods with interview and observation. Results: The observation results showed that school canteen in SD Negeri Mangunsari 03 Salatiga only has small room near 4th grade class. Nevertheless, SD Negeri Mangunsari 03 Salatiga tried to build healthy canteen in many ways, such as using display window to kept food, go strich toward food that using addictive, sweetern, and clip. Conclusion: Some of rule on school canteen in SD Negeri Mangunsari 03 is not match with Guidelines of Ministry of Health no 1429/2006; Guidelines of Food Safety in elementary school based on Ministry of Health regulalion in 2011, and Guidelines of School Canteenâs food safety from BPOM in 2012 but lagerly already followed decree of minister of health of the Republic of Indonesia no 942/Menkes/SK/VII/2003.